The Influence of Corporate Social Responsibility on Firm Value in Energy Sector Companies Listed on The Indonesia Stock Exchange During The 2018–2024 Period - Desi Kurniawati; Husnul Khotimah; Muhammad Ikhsan Febriyanto (IJESS International Journal of Education and Social Science, 2026)
This study aims to analyze the impact of Corporate Social Responsibility (CSR) on firm value among energy sector companies listed on the Indonesia Stock Exchange (IDX) during the 2018–2024 period. The study is motivated by the importance of implementing CSR as a form of corporate social and environmental responsibility; such implementation is expected to enhance the company's reputation and improve investor perception, thereby leading to an increase in firm value. A quantitative approach employing multiple linear regression analysis is used in this study. The population consists of all energy sector companies listed on the IDX, while the sample was selected using purposive sampling based on criteria regarding the availability of annual reports and CSR disclosures throughout the observation period. The independent variable is CSR, measured by a CSR disclosure index based on Global Reporting Initiative (GRI) guidelines, whereas the dependent variable is firm value, proxied by Tobin’s Q.